2013
DOI: 10.1038/cddis.2013.474
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-derived immunoglobulin G promotes tumor cell growth and proliferation through inducing production of reactive oxygen species

Abstract: Cancer cells have been found to express immunoglobulin G (IgG), but the exact functions and underlying mechanisms of cancer-derived IgG remain elusive. In this study, we first confirmed that downregulation of IgG restrained the growth and proliferation of cancer cells in vitro and in vivo. To elucidate its mechanism, we carried out a co-immunoprecipitation assay in HeLa cells and identified 27 potential IgG-interacting proteins. Among them, receptor of activated protein kinase C 1 (RACK1), ras-related nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 45 publications
3
44
0
5
Order By: Relevance
“…The role of physiological ROS as a signalling molecule in key signalling pathways (D'Autréaux and Toledano, 2007) including proliferation (Ruiz-Ginés et al, 2000;Valarde et al, 2004;Lister et al, 2011;Wang et al, 2013) has been shown in a number of studies. In order to illustrate that physiological ROS might be involved in maintaining high growth rates, a cellular proliferation assay was performed in the presence of 10 mM NAC.…”
Section: Cancer Cells Are Addicted To Elevated Levels Of Basal Rosmentioning
confidence: 99%
“…The role of physiological ROS as a signalling molecule in key signalling pathways (D'Autréaux and Toledano, 2007) including proliferation (Ruiz-Ginés et al, 2000;Valarde et al, 2004;Lister et al, 2011;Wang et al, 2013) has been shown in a number of studies. In order to illustrate that physiological ROS might be involved in maintaining high growth rates, a cellular proliferation assay was performed in the presence of 10 mM NAC.…”
Section: Cancer Cells Are Addicted To Elevated Levels Of Basal Rosmentioning
confidence: 99%
“…It seems that IgG can enhance the growth and proliferation of tumor cells via inducing the production of ROS at low level. These findings provide new clues for understanding tumor proliferation and designing cancer therapy [68]. Activation induced cytidine deaminase (AID), which is essential for both class switch recombination and somatic hypermutation, was also reported to be expressed in six breast cancer cell lines by nested RT-PCR [71].…”
Section: Immunoglobulin Expression By Tumor Cellsmentioning
confidence: 95%
“…Curiosamente, western blotting com mAb ligante de CEA 1F5H2 aponta para duas bandas, de aproximadamente 25 e 50 kDa, também identificadas por anti-FGF2 3F12E7 IgG. Por apresentarem um padrão de peso molecular característico de fragmentos correspondentes às cadeias leve e pesada de imunoglobulinas, é bastante provável que elas sejam o resultado da interação do anticorpo secundário HRPO-anti-IgG de camundongo, utilizado como parte da revelação do ensaio de western blotting, com imunoglobulinas endógenas presente na massa tumoral (Mancardi DA et al, 2013;Wang J et al, 2013), conforme observa-se na Fig. 13C.…”
Section: Resultados E Discussão Parcialunclassified
“…Trabalhos na literatura relatam o papel desse fator na neovascularização de tumores (Kibbey MC et al, 1992;Miyake H et al, 1996;Wang Y et al, 1997). Ensaios in vivo com linhagens tumorais mostram uma correlação entre hiper-regulação da expressão de FGF2 e um aumento da neovascularização e potencial metastático (Miyake H et al, 1996).…”
Section: Fator 2 De Crescimento De Fibroblastosunclassified
See 1 more Smart Citation